A DARK ENERGY CAMERA SEARCH FOR MISSING SUPERGIANTS IN THE LMC AFTER THE ADVANCED LIGO GRAVITATIONAL-WAVE EVENT GW150914 - Annis, J.; Soares-Santos, M.; Berger, E.; Brout, D.; Chen, H.; Chornock, R.; Cowperthwaite, P. S.; Diehl, H. T.; Doctor, Z.; Drlica-Wagner, A.; Drout, M. R.; Farr, B.; et al. (Iop Publishing Ltd, 2016)
The collapse of a stellar core is expected to produce gravitational waves (GWs), neutrinos, and in most cases a luminous supernova. Sometimes, however, the optical event could be significantly less luminous than a supernova and a direct collapse to a black hole, where the star just disappears, is possible. The GW event GW150914 was detected by the LIGO Virgo Collaboration via a burst analysis that gave localization contours enclosing the Large Magellanic Cloud (LMC). Shortly thereafter, we used DECam to observe 102 deg(2) of the localization area, including 38 deg(2) on the LMC for a missing supergiant search. We construct a complete catalog of LMC luminous red supergiants, the best candidates to undergo invisible core collapse, and collected catalogs of other candidates: less luminous red supergiants, yellow supergiants, blue supergiants, luminous blue variable stars, and Wolf-Rayet stars. Of the objects in the imaging region, all are recovered in the images. The timescale for stellar disappearance is set by the free-fall time, which is a function of the stellar radius. Our observations at 4 and 13 days after the event result in a search sensitive to objects of up to about 200 solar radii. We conclude that it is unlikely that GW150914 was caused by the core collapse of a relatively compact supergiant in the LMC, consistent with the LIGO Collaboration analyses of the gravitational waveform as best interpreted as a high mass binary black hole merger. We discuss how to generalize this search for future very nearby core-collapse candidates.
Keywords: galaxies: individual (LMC); gravitational waves; Magellanic Clouds; supergiants; supernovae: general